DIGITALISASI UMKM SEBAGAI PENGGERAK EKONOMI KREATIF: PELUANG DAN TANTANGAN - Cherin Putri Pratiwi (CURVE: Journal of Economic, Business and Accounting, 2025)
Micro, Small, and Medium Enterprises (MSMEs) contribute 6061.9% of Indonesia's GDP and absorb 97% of the national workforce, while the creative economy is growing rapidly, accounting for 7-8% of GDP, with subsectors such as fashion, culinary, and technology applications. Digitalization is crucial for addressing challenges such as low literacy and uneven infrastructure, while simultaneously capitalizing on e-commerce and social commerce opportunities. This study aims to analyze the role of MSME digitalization as a driver of the creative economy, identify opportunities and challenges, and formulate strategies for strengthening digital transformation. The research method uses a qualitative descriptive approach through a literature review of academic literature, reports from Bappenas, LIPI, and BPS for the 2022-2025 period, with content analysis and source triangulation for validity. The results show that digitalization drives product innovation, operational efficiency via cloud accounting and analytics, access to fintech platforms such as QRIS and crowdfunding, and global market expansion through marketplaces like Shopee and TikTok Shop. Opportunities include viral Reels/Shorts promotion and startup incubation, while challenges include low digital literacy (only 30% of MSMEs are optimal), rural infrastructure gaps, and cybersecurity. Integrated solution strategies such as the Digital Talent Scholarship, Palapa Ring, and the IDR 500 trillion Digital KUR (People's Business Credit) program can bring 40 million MSMEs online by 2025.